Spatial Manifestation of Migration Flows of Internally Displaced Persons in Ukraine - Dzhaman, V. O.; Dzhaman, Ya. V. (Ukrainian Geographical Journal, 2024)
The problem of occurrence and legal regulation in Ukraine of “internally displaced persons” (IDP) due to Russian aggression against Ukraine has been considered. The scope and particularities of the dynamics of the number of IDPs in Ukrainian regions were analyzed. The question of IDP’s social safety net is raised. First IDPs appeared in Ukraine with the beginning of Russian war aggression in 2014 and active hostility, resulting in the annexation of the Autonomous Republic of Crimea and the City of Sevastopol and the temporary occupation of part of the territory of Luhansk Region and Donetsk regions. Legal regulation for this category of people required the adoption of such legal instruments as the Cabinet of Ministers, Ukraine, Resolution on “Registration of Internally Displaced Persons,” and Safeguards for the Rights and Freedoms of Internally Displaced Persons Act, Ukraine. In the first period (hybrid war), most IDPs migrated within small distances. Displacements were intro-oblast, or those to oblasts that neighbored temporarily occupied territories: the Donetsk and the Luhansk oblasts had concentrated 54.4% of all IDPs; the oblasts that directly neighbored the temporarily occupied territories and the ATO zone (first-order neighbors: Kharkiv, Dnipropetrovsk, Zaporizhzhia, and Kherson) saw 19.0% IDPs; second-order neighbors took 7.5% of forced migrants; Kyiv and Kyiv Oblast were the most attractive territories among all oblasts distant from temporarily occupied territories and the ATO zone (15.7%); the least number of IDPs moved to the most distant western regions of Ukraine. There were 1.4592 million internally displaced persons who registered in said quality as of the beginning of 2021. The full-scale war had caused mass displacements in Ukraine to significant distances. It was 10.1 million Ukrainians who became forced migrants in the first month of the war, inclusive of nearly 6.5 million IDPs. The total number of registered internally displaced persons had become stable in 2023 at 3.5–3.7 million people. The mid-2024 showed the figure of 3.3147 million IDPs. Spatial differences in IDP settlement and dynamics in Ukraine have been established depending on the geography of hostilities, closeness to temporarily occupied territories, and distance from the borderline with the Russian Federation and Belarus. New settlement areas are outlined as follows: south-western, central, northern, capital, north-eastern, eastern, and southern.